Crystal transformation of 2D tungstic acid H2WO4 to WO3 for enhanced photocatalytic water oxidation - Ke, J.; Zhou, H.; Liu, J.; Duan, Xiaoguang; Zhang, H.; Liu, Shaomin; Wang, Shaobin (Academic Press, 2018)
New photocatalytic materials for stable reduction and/or oxidization of water by harvesting a wider range of visible light are indispensable to achieve high practical efficiency in artificial photosynthesis. In this work, we prepared 2D WO 3 ·H 2 O and WO 3 nanosheets by a one-pot hydrothermal method and sequent calcination, focusing on the effects of crystal transformation on band structure and photocatalytic performance for photocatalytic water oxidation in the presence of electron acceptors (Ag + ) under simulated solar light irradiation. The as-prepared WO 3 nanosheets exhibit enhanced rate of photocatalytic water oxidation, which is 6.3 and 3.6 times higher than that of WO 3 ·H 2 O nanosheets and commercial WO 3 , respectively. It is demonstrated that the releasing of water molecules in the crystal phase of tungstic acid results in transformation of the crystal phase from orthorhombic WO 3 ·H 2 O to monoclinic WO 3 , significantly improving the activity of photocatalytic water oxidation in the presence of Ag + because the shift-up of conduction band of WO 3 matches well with the electrode potential of Ag + /Ag(s), leading to efficient separation of photoinduced electrons and holes in pure WO 3 nanosheets.